Plug Formation Imaged Beneath the Active Craters of Sakurajima Volcano With Muography. Issue 17 (12th September 2019) - Oláh, László; Tanaka, Hiroyuki K.M.; Ohminato, Takao; Hamar, Gergő; Varga, Dezső
Abstract: Sakurajima Muography Observatory captured the formation of a volcanic plug beneath the Showa crater with a spatial resolution of ∼60 m in accordance with the end of the eruption episode of Showa crater and the reactivation of Minamidake crater. The increase of average density was observed with above 3  σ standard deviation for both above the floor of Minamidake crater and beneath the floor of Showa crater, respectively, being interpreted as volcanic ejecta deposition and the formation of a volcanic plug laterally extended within a few hundreds of meters. Plain Language Summary: Muography is an imaging technique that provides information about the amount of material across kilometer‐thick geological structures by the measurement of the yield of cosmic rays, similarly to X‐raying of human body. We applied muography to capture two muon images of Minamidake and Showa craters of Sakurajima volcano before and after the shift of eruption activities occurred between the two craters at the end of 2017. The comparison of the images revealed the presence of increased material across the activated Minamidake and beneath the deactivated Showa crater. Muography detected the formation of a magma plug in the conduit of Showa crater that was not detected earlier by any other geophysical technique. These results demonstrate the applicability of cosmic muon imaging for monitoring of magma movements inside active volcanoes. Key Points: Two muographic images were taken across the erupting Sakurajima volcano with a spatial resolution of 60 m Increased average densities were observed beneath the deactivated crater after the shift of eruption sequence Muography data suggest that uprising magma formed a plug in the conduit of Showa crater